Monsoon climate impact on drip water geochemistry at Niah Great Cave, NW Borneo, Malaysia: Evaluating the spatial and temporal trends - Prasanna, Mohan Viswanathan; Chidambaram, S.; Nagarajan, R.; Anand Kumar, A. (2016)
A total of nine drip water samples were collected at Trader Cave Entrance (TCE), Cave Center (CC) and Painted Cave Entrance (PCE) of Niah Great Cave, NW Borneo, Malaysia during monsoon period to understand the spatial and temporal variations of drip water geochemistry by comparing with the summer season data. The collected samples were analyzed for physico-chemical parameters using standard procedures. The chemical components of the limestone host rock indicate that its dominant mineral component is low magnesium calcite. Interpretation of data shows that higher ionic concentration was noted in TCE followed by CC and PCE in monsoon. However the ionic concentration in summer season was much higher than the monsoon season. Ca-HCO3 is the most common water type recognized in the study site which indicates the carbonate dissolution by water-rock interaction. Higher ionic strength values were noted in TCE drip waters indicating high flushing rate of recharge water, which released more ions into the drip water. The saturation index of calcite and aragonite are in near saturation to over saturation state, whereas magnesite and dolomite are under saturation condition. The results of factor analysis reveal that the geochemistry of drip water is mainly controlled by the carbonate mineral-water equilibrium.